Mekanisme ‘gacha’ dan ‘parasocial interaction’ pemain gim seluler - Pradhipta, Amelia Yeza (Faculty of Communications Science, Dr. Soetomo University, 2021)
This article elaborates how parasocial interaction in freemium mobile game may motivate users to spend money for Gacha, an in-game virtual lottery mechanism in which users will randomly get one or several in-game items with different levels of rarity. The literature review method was used for this article which began with thorough explanations of the main concepts, such as freemium seluler game, microtransactions, Gacha mechanism, and parasocial interaction. This article concludes that seluler game developers creatively designed the game characters to be well-liked by the players through characterization and visual aspects that aesthetically pleasing in hope that gamers may experience parasocial interaction and relationship with one of the characters, which may turn into character attachment. The interaction and attachment will then encourage the players to keep spending money through microtransactions to get the characters or virtual cosmetic items they want through Gacha.